Quantitative Determination of Methanol in Plant Water Produced in Mashhad by Spectrophotometry Method - GH Karimi; M Hassanzadeh; N Shahidi; Z Samie (Institue of Medicinal Plants, ACECR, 2008)
Background: Methanol is a toxic aliphatic alcohol that is widely used in industry as a solvent. Poisonings occur from accidental or awareness ingestion of it. Objective: In this study, the amount of methanol in ten plant water was evaluated. Methods: Five samples from each plant waters that related to six factories collected and analyzed by spectrophotometric method. Results: The results showed that the highest (1477.7  23.8 ppm) and the lowest (79.4  3 ppm) amount of methanol was related to dill and egiptial willow water, respectively. Conclusion: Since, the chronic use of plant water may induce methanol toxicity, it is recommended to determine a safe limit for it.